Synthesis of Bi2O3/TiO2 nanostructured films for photocatalytic applications. Issue 18 (15th December 2018) - Correia, F.C.; Calheiros, M.; Marques, J.; Ribeiro, J.M.; Tavares, C.J.
Abstract: Dendritic growth of bismuth oxide nanostructured films was accomplished by reactive magnetron sputtering. The deposition of the Bi2 O3 template layers was adapted to abide a vapour-liquid-solid mechanism in order to develop a 3D growth morphology with high surface area templates for photocatalytic applications. TiO2 photocatalytic thin films were deposited at a later stage onto Bi2 O3 layers. The obtained heterostructured films were characterized by scanning electron microscopy, X-ray diffraction and atomic force microscopy. Additionally, the photocatalytic efficiency was assessed by conducting an assay using methylene blue dye as testing pollutant under a UV-A illumination. The photocatalytic tests revealed that the Bi2 O3 layers functionalized with TiO2 thin films are more efficient at degrading the pollutant, by a factor of 6, when compared with the individual layered films.